BIM and Sustainable Construction Integration: An IFC-Based Model - Bahriye İlhan; Hakan Yaman (Megaron, 2015)
Building Information Modeling (BIM) and sustainability are the two current and emerging movements in the architecture, engineering and construction (AEC) industry. Even though the importance of Green BIM is recognised, there are some barriers to a functional inclusion such as lack of measured sustainable strategies' direct access into BIM. Their integration has a great impact on sustainable construction. Accordingly, this study focuses on setting up a substructure of the Industry Foundation Classes (IFC)–based model for BIM and sustainability integration. The main purpose is to fill the gap of BIM integration with standards of sustainable construction by providing a guideline for the design team to address the sustainable features of the project during the design stage. It provides an integrated platform to work on and facilitates the green documentation generation for getting green building certification. Firstly, the property sets are developed in the IFC structure in order to designate the green properties into BIM projects. This process includes the investigation of major categories and criteria of the Green Building Assessment Systems, determination of the possible categories for IFC schema, creation of the property sets and acquisition of the related data. Following this, the green materials database and library are created to get the sustainable data for the assessment. Next, the BIM model is generated based on the green materials. The assessment tool for the data calculation is presented as the last process of the basis for the integrated model. Finally, the applicability of the model is discussed for future studies.